Pengaruh Media Kartu Huruf terhadap Keterampilan Membaca Siswa Kelas I MIN 11 Hulu Sungai Selatan - Noor Fitriah (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2023)
Early reading focuses on reading simple words of Bahasa Indonesia and sentences using pronunciation and intonation punctuation properly. Students are able to read simple words, students are required to know letters and be able to pronounce them correctly. So that, in learning early reading teachers need to use of interesting media. This research is a quantitative research with a quasi-experimental method approach which aims to determine an influence of letter card media on the reading skills of grade 1 students at MIN 11 Hulu Sungai Selatan. The sampling technique was simple random sampling consisting of 1A and 1C classes with a total of 46 students. The results of the study were based on the t-test (count) to obtain a tcount=2.772 with a significance level of 5%, namely 0.05, so ttable=2.015 means tcount > ttable (2.772 > 2.015). In accordance with the test criteria, namely if tcount > ttable then Ha is accepted and Ho is rejected, meaning that there is an influence on the use of letter card media at MIN 11 Hulu Sungai Selatan